Integrated Informational and Analytical System of Calculating Economic Indices at Enterprises of Public Catering - M. A. Belyaeva; A. A. Gazhur; V. I. Perov; O. K. Bezotosova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article provides a review of existing software for calculation of calorie content and food value of culinary dishes. A relevant sub-system was designed for market research and sociological survey. Based on analysis of existing software an integrated informational and analytical system was developed meant for calculating prime cost and price of culinary dishes depending on the norms of ingredients’ putting and for calculating economic indices. The structural and parametric analysis of data includes correlation and regressive analysis and the matrix of abnormal conditions. The sub-system of structural and parametric modeling and identification is used for the calculation. The sub-system  of  calculating  economic  indices  automation  was  developed  by  MS  Excel  and  Visual  Basic  For Application. It provides calculation of the number of sold culinary dishes and database for calculation and technical and technological cards, which are accompanied by visual screen forms. Importing data from MS Excel to the imitation system AnyLogic gives an opportunity to analyze dynamics of economic indices, forecast finance situation at the public catering enterprise. The integrated informational and analytical system could be useful for enterprises, executives, technologists, managers in restaurant business and could be introduced not only in the catering system of the Russian Plekhanov University of Economics but in other public catering enterprises.